A successful treatment of severe systemic lupus erythematosus caused by occult pulmonary infection-associated with hemophagocytic syndrome: A case report. Issue 19 (May 2018) - Shi, Weihong; Duan, Mingyang; Jie, Ligang; Sun, Weifeng
Abstract: Rationale: A 27-year-old woman with a history of systemic lupus erythaematosus (SLE) developed hemophagocytic syndrome (HPS) secondary due to an unrecognized infection that led to severe SLE with a prolonged recovery. Patient concerns: The patient showed a high spiking fever and myalgia. Laboratory data revealed pancytopenia and immunological abnormalities. Pulse methylprednisone plus intravenous immunoglobulin (IVIG) failed to improve the clinical symptoms and laboratory data. Diagnoses: As activated macrophages with hemophagocytosis were confirmed in bone marrow histology, the patient was diagnosed as having reactive HPS. Interventions and outcomes: Her reactive HPS was successfully treated with intravenous antibiotics and was followed by oral prednisolone and hydroxychloroquine maintenance therapy. Lessons: In severe SLE, patients with persistent high fever, cytopenia, and elevated levels of serum ferritin and liver enzymes should be strongly suspected of reactive HPS, and aggressive examination, such as bone marrow biopsy, needs to be considered for early diagnosis and proper treatment.